Destination Foodscape – A Holistic Conceptual Framework - Bernardo, Edgar; Agapito, Dora; Guerreiro, Manuela (Journal of Tourism, Sustainability and Well-being, 2021)
While destination foodscape experience is a subject of growing interest, most studies have been dominated by a management and marketing approach. This theoretical research builds upon current literature on destination foodscape and identifies diverse elements that can influence the destination foodscape experience. The research contributes to different social science fields by drawing a multidisciplinary holistic conceptual framework that can help to better understand the importance of food systems. This reflection indicates that place and space as well as performance in connection with consumption are essential for foodscape destination analysis. Findings suggest that by complementing different social sciences, considering different academic points of view and taking different stakeholders into account, the proposed holistic conceptual framework allows for a deeper and wider understanding of destination foodscape.